2020
DOI: 10.1016/j.ejmech.2019.111893
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolone structural motif in medicinal chemistry: Retrospect and prospect

Abstract: a b s t r a c tThe pyrazolone structural motif is a critical element of drugs aimed at different biological end-points. Medicinal chemistry researches have synthesized drug-like pyrazolone candidates with several medicinal features including antimicrobial, antitumor, CNS (central nervous system) effect, anti-inflammatory activities and so on. Meanwhile, SAR (Structure-Activity Relationship) investigations have drawn attentions among medicinal chemists, along with a plenty of analogues have been derived for mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(68 citation statements)
references
References 152 publications
1
64
2
Order By: Relevance
“…Similarly, they have used another potent SARS-CoV 3CLpro inhibitor (i.e. Benzotriazole ester derivative) for designing the target molecule, which was developed by the Wong research group in 2006 90 . They synthesized the designed SMIs via Scheme 21 .…”
Section: Chemical Synthesis Of Sars-cov 3clpro Inhibitorsmentioning
confidence: 99%
“…Similarly, they have used another potent SARS-CoV 3CLpro inhibitor (i.e. Benzotriazole ester derivative) for designing the target molecule, which was developed by the Wong research group in 2006 90 . They synthesized the designed SMIs via Scheme 21 .…”
Section: Chemical Synthesis Of Sars-cov 3clpro Inhibitorsmentioning
confidence: 99%
“…The broad-spectrum of pharmacological properties of pyrazolone derivatives have been reported including antimicrobial, antitumor, CNS activity, anti-inflammatory, antioxidant, antitubercular, antiviral, lipid-lowering, antihyperglycemic, and protein inhibitory activities. [34] Furthermore, recently, Tao et al showed EGFR/HER-2 tyrosine kinase inhibitory activity of 1Hpyrazole-1-carboxamide analogs. [35] A series of 1H-pyrazole-1carbothioamide has been also reported for anticancer activity on MCF-7 cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In this regard, pyrazolone derivatives are of particular interest because, based on them, an entire class of analgesic-antipyretics has been developed to be successfully applied in clinical practice for a long time. 11,12 The predecessor of this pyrazolone family is phenazone (antipyrine) (1) (Fig. 1) that is still part of some combination drugs, e.g., A/B otic drops (ear drops).…”
Section: Introductionmentioning
confidence: 99%
“…1) that is still part of some combination drugs, e.g., A/B otic drops (ear drops). 13 Research in recent years has shown that the pyrazolone core is a universal structure 14 to develop substances with various types of biological action including antimicrobial, 11 antitubercular, 15,16 antiviral, 17 anticancer, [18][19][20][21] analgesic, 22 anti-inammatory, 23 antioxidant, 24 and anti-diabetic 25 activities as well as action on CNS, 26,27 etc.…”
Section: Introductionmentioning
confidence: 99%